Design built-in self-test for control sequencer circuit using xilinx - Mohamed Isa, Nurul Aini (2004)
An alternative to applying test vectors from an external tester is a built-in selftest (BIST). The development of BIST based on determined test pattern generation (random pattern generation) using LFSR. BIST strategies use pseudo-random sequences as the test sequences. In part of the design process BIST require extra pin which become from three ports such as sequencer circuit (CUT), Test Pattern Generation (TPG) and Linear Feedback Shift Register (LFSR). The sequencer circuit is a circuit that displayed the outputs of sequences number. It was chosen as a sample of IC subsystem due to its widely used in most Digital-Signal-processing (DSP) chip. Sequencing is an assembly term refers to arranging axial/radial components in their order of insertion sequence, and to prepare new tape/reel by a sequencer.